A Subtitling Analysis Of Imperative Sentence Found In Need For Speed By Pein Akatsuki - Juniarta, Tommi; , Dr. Dwi Haryanti, M. Hum (2016)
This research focuses on the subtitling analysis of imperative sentence in Need for Speed movie by Pein Akatsuki using Quirck's theory about sentence and Baker's theory about equivalence. The objective of this research are (1) to identify the type of imperative sentence found in Need for Speed movie and (2) to describe the equivalence of imperative sentence found in Need for Speed movie. The type of this research is descriptive qualitative. The object of this research is Need for Speed movie script. The researcher uses documentation technique to collect the data. The researcher uses triangulation to prove the validity of this research where the data sources are from movie and informant. The researcher obtain 209 data of imperative sentence in Need for Speed movie script. There are imperative sentence with subject 20,57%, imperative sentence without subject 66,03%, imperative sentence with let 7,66%, and negative imperative sentence 5,74%. The most imperative sentence used in this movie is imperative sentence without subject (based on verb). The equivalence of imperative sentence is divided into equivalence and non equivalence subtitling. The equivalence occurs in 1374 data or 100% of data and none of them belongs to non equivalence subtitling.